Engineering of Recombinant Sheep Pox Viruses Expressing Foreign Antigens - Olga Chervyakova; Elmira Tailakova; Nurlan Kozhabergenov; Sandugash Sadikaliyeva; Kulyaisan Sultankulova; Kunsulu Zakarya; Rinat A. Maksyutov; Vitaliy Strochkov; Nurlan Sandybayev (Microorganisms, 2021)
Capripoxviruses with a host range limited to ruminants have the great potential to be used as vaccine vectors. The aim of this work was to evaluate attenuated sheep pox virus (SPPV) vaccine strain NISKHI as a vector expressing several genes. Open reading frames SPPV020 (ribonucleotide kinase) and SPPV066 (thymidine kinase) were selected as sites for the insertion of foreign genes. Two integration plasmids with expression cassette were designed and constructed. Recombinant SPPVs expressing an enhanced green fluorescent protein (EGFP) (rSPPV(RRΔ)EGFP and rSPPV(TKΔ)EGFP), Foot-and-mouth disease virus capsid protein (VP1), and Brucella spp. outer membrane protein 25 (OMP25) (rSPPV(RRΔ)VP1A-(TKΔ)OMP25) were generated under the transient dominant selection method. The insertion of foreign genes into the SPPV020 and SPPV066 open reading frames did not influence the replication of the recombinant viruses in the cells. Successful foreign gene expression in vitro was assessed by luminescent microscopy (EGFP) and Western blot (VP1 and OMP25). Our results have shown that foreign genes were expressed by rSPPV both in permissive (lamb testicles) and non-permissive (bovine kidney, saiga kidney, porcine kidney) cells. Mice immunized with rSPPV(RRΔ)VP1A-(TKΔ)OMP25 elicited specific antibodies to both SPPV and foreign genes VP1 and OMP25. Thus, SPPV NISKHI may be used as a potential safe immunogenic viral vector for the development of polyvalent vaccines.